Antioxidant and Anti-Inflammatory Properties of a Thuja occidentalis Mother Tincture for the Treatment of Ulcerative Colitis - Miruna Silvia Stan; Sorina Nicoleta Voicu; Sonia Caruntu; Ionela Cristina Nica; Neli-Kinga Olah; Ramona Burtescu; Cornel Balta; Marcel Rosu; Hildegard Herman; Anca Hermenean; Anca Dinischiotu (Antioxidants, 2019)
Inflammatory bowel disease (IBD) represents a group of chronic autoimmune and idiopathic disorders that are characteristic of industrialized countries. In contrast to drug therapies, which exert several side effects, herbal remedies have constantly attracted the attention of researchers. Therefore, in the present study, a mother tincture (MT) from fresh, young, non-woody Thuja occidentalis L. branches with leaves was obtained using distillation-based techniques. Further, this was used to assess its in vitro and in vivo antioxidant activities and anti-inflammatory properties, and to validate it as a potential phytotherapeutic treatment for IBD. The characterization of the tincture included common phytochemical screening assays for antioxidant capacity measurement, cell viability assays on Caco-2 colon cells, and in vivo assessment of antioxidant and anti-inflammatory effects by histopathological and ultrastructural analysis of the intestinal mucosa, measurement of reduced glutathione, lipid peroxidation, and gene expression of the inflammation markers (interleukin-6 and tumor necrosis factor-α) in intestine after oral administration to an experimental mouse model of colon inflammation (colitis) developed by intrarectal administration of 2,4,6-trinitrobenzenesulfonic acid (TNBS). Our study proved that administration of 25 or 50 mg T. occidentalis MT/kg of body weight/day by gavage for 7 days succeeded in inhibiting the inflammatory process induced by TNBS in the intestine, most probably because of its rich contents of flavonoids and phenolic compounds. These data could contribute to the formulation of therapeutic products based on T. occidentalis that could come to the aid of IBD patients.